2016
DOI: 10.20524/aog.2016.0090
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge acquired, satisfaction attained and attitudes towards shared decision making in colorectal cancer screening

Abstract: BackgroundIntroducing shared decision making (SDM) in colorectal cancer (CRC) screening requires patients to acquire appropriate knowledge. We aimed to describe the knowledge attained by subjects with a family history of CRC.MethodsConsecutive patients attending the gastroenterology clinic for a CRC family history were invited to take part in a cross-sectional survey. Attitudes towards SDM, satisfaction with the information received, knowledge currently achieved, and relevant influencing factors were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The latter participants were older and had more physical symptoms and functional limitations at the beginning of adjuvant treatment. Previous studies evaluating patient preferences revealed that breast cancer patients are younger, healthier, and have more active or cooperative roles [5, 26] while individuals with colon cancer would like to be informed and involved in decision-making, but do not necessarily want to make autonomous treatment choices and many prefer a more passive role [27]. In addition, the greater psychological impact of breast cancer, with more symptoms of anxiety, depression, and somatization is not only explained by the fact that it affects younger patients, at a time of maximum professional and family activity, but also by significant changes in appearance (hair loss, mastectomy, weight gain due to hormonotherapy), physical symptoms, and uncertainty about prognosis [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…The latter participants were older and had more physical symptoms and functional limitations at the beginning of adjuvant treatment. Previous studies evaluating patient preferences revealed that breast cancer patients are younger, healthier, and have more active or cooperative roles [5, 26] while individuals with colon cancer would like to be informed and involved in decision-making, but do not necessarily want to make autonomous treatment choices and many prefer a more passive role [27]. In addition, the greater psychological impact of breast cancer, with more symptoms of anxiety, depression, and somatization is not only explained by the fact that it affects younger patients, at a time of maximum professional and family activity, but also by significant changes in appearance (hair loss, mastectomy, weight gain due to hormonotherapy), physical symptoms, and uncertainty about prognosis [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…A focus on shared decision makingwhere a decision is made in collaboration with a health professionalwould perhaps have been a better alternative for some participants in this study. Several studies found that in making CRC screening decisions most individuals prefer to consult their physician [52][53][54]. This might be especially the case for vulnerable patients such as racial/ethnic minorities and lowincome individuals as these groups exhibit lower screening uptake [55].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Physician‐reported barriers are time constraints, a lack of agreement with certain key elements of SDM, and a lack of practical applicability because of patient characteristics or the nature of the medical situation . There is also evidence for a supportive attitude toward SDM on the side of the patients . However, patients tend to underestimate their contribution in the process and do not often recognize the importance of their personal preferences .…”
Section: Introductionmentioning
confidence: 99%